Awake Fiberoptic Intubation: The First Mandatory Choice of Difficult Airway – A Report of Two Cases - T. Krishna Prasad; C. Dhinesh Kumar; Abinaya Devi; S. Vijay Narayanan (Indian Journal of Medical Specialities)
We may have many devices in this 21st century, which can be used to secure the airway in patients who have been predicted to have a difficult airway. There are many studies about difficult airways and suggested various devices such as flexible fiberoptic scope, video laryngoscope, and the specialized intubating laryngeal mask airway and they ended up concluding one device better than another. Furthermore, ET intubation requires continued practice and carries with it its own set of complications. Technical problems with the placement of endotracheal tubes have been the most frequent cause of anesthetic deaths in published analyses from all over the world. The basic responsibility of an anesthesiologist is to maintain adequate gas exchange in patients by securing a patent airway through a proper device. Fiberoptic bronchoscopy and intubation have the advantage of being easier, with shorter intubation time and continuous oxygenation and ventilation throughout the procedure, especially in the case of children. We report two such cases, where “Awake flexible fiberoptic-guided intubation” was considered the only desirable choice.